PENGARUH HARAPAN PENGAJAR TERHADAP MOTIVASI DAN PRESTASI SISWA DI KELAS - Setiadi Umar; Christin . (Bina Ekonomi, 2010)
This  research  refers  to the research conducted by Rosenthal  and Jacobson  (1968), which finds  that students'  intellectual  development  is influenced by their teacher  expectations  and how these expectations are communicated  to them. Therefore, this study hypothesizes that positive teacher expectations and behavior in experimental classes for one semester would strengthen students’ effort and motivation in achieving higher performance in the experimental classes.  In this experiment, students / respondents were not isolated from external environmental influences,  such as from the  influence of other  their 'regular’  classes, lecturers, as well as  their  classmates. The method used  in this study was experimentation  method  using two teachers  and two subjects. Each teacher taught two classes of one same subject, which were divided into experimental group and control group. The  result of  this experimentation shows  that  the students'  achievement  in both of the experimental  classes is not different  significantly  than  those in regular/ control classes.